Research data supporting "Using public transport system for sustainable urban freight delivery" - Pivtorak, Halyna; Švadlenka, Libor (My University, 2025)
The monograph explores innovative solutions for sustainable urban freight delivery through the integration of public transport systems. Focusing on the crowdshipping model, where everyday commuters deliver parcels during their regular trips, the study highlights economic, environmental, and social benefits. Using extensive survey data from Ukraine and the Czech Republic, the authors analyze citizens' willingness to work as crowdshippers and identify key factors influencing participation, applying fuzzy AHP and multinomial logit models. A case study from Pardubice demonstrates the modeling of parcel flows with PTV Visum software. The findings underline the potential of combining public transport with urban freight to reduce emissions, traffic congestion, and delivery costs. Recommendations include establishing supportive legal frameworks, investing in infrastructure such as parcel lockers, and developing digital platforms to facilitate efficient crowdshipping. The monograph offers a roadmap for implementing sustainable and inclusive urban logistics solutions.
Keywords: crowdshipping; sustainable urban logistics; public transport integration; last-mile delivery; e-commerce; freight mobility